Mixed Farming Systems in the tropics, a CGIAR Initiative in 5 countries. Challenges and Collaboration in Laos - Mienmany, Soytavanh (International Center for Tropical Agriculture, 2023)
This Initiative addresses the Sustainable intensification (SI) of Mixed farming systems (MFS). By SI, we mean the production of more food on the same piece of land while reducing the negative environmental impact. MFS cover about 2.5 billion ha of land globally. In the developing world, MFS supply around 75% of milk, 60% of meat, and 41–86% of cereals consumed. These farming systems occur in nearly all agro-ecological zones, with an enormous variety of climatic and soil conditions and livelihood patterns. In SEast Asia the initiative is working in Bangladesh, Nepal and Laos. In Laos, the Initiative is focusing on two sites, one in the northern uplands where mostly maize is grown but farmers who are now transitioning into more livestock raising and fodder crops. In the southern lowlands the initiative focus on areas where coffee was the dominant crop, but recently those lands were converted to cassava. Moreover, some forests have been cleared for cassava. These changes bring along challenges and tradeoffs related to food security, poverty reduction and environmental conservation. To address these challenges, a systems approach is needed that takes into account the performance of different components of the SI-MFS and their interactions. Some farmers in both sites have been practising MFS for many years but have had limited if any support from research agencies and development projects. This workshop will discuss factors that influence farmers’ decision-making on their livelihood choices and farm practices and will be a starting point to discuss on the possibility to develop coherent innovations for the co-design of SI-MFS and support farmers and local stakeholders into a trajectory towards SI.